2020
DOI: 10.1002/mrm.28247
|View full text |Cite
|
Sign up to set email alerts
|

An analytical solution to the dispersion‐by‐inversion problem in magnetic resonance elastography

Abstract: Purpose Magnetic resonance elastography (MRE) measures stiffness of soft tissues by analyzing their spatial harmonic response to externally induced shear vibrations. Many MRE methods use inversion‐based reconstruction approaches, which invoke first‐ or second‐order derivatives by finite difference operators (first‐ and second‐FDOs) and thus give rise to a biased frequency dispersion of stiffness estimates. Methods We here demonstrate analytically, numerically, and experimentally that FDO‐based stiffness estima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…If there are not enough pixels sampled per wavelength, discretization effects when estimating derivatives can bias the results. Depending on the inversion and the derivative kernel used, this can cause about a 4% error when there are 9‐10 pixels per wavelength, but the error rapidly increases with fewer pixels per wavelength 79,83,84 . Conversely, when the wavelength becomes much larger than the pixel size, the discrete derivative operations required for some inversion methods are highly affected by low SNR.…”
Section: Good Practices For Mre Publicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…If there are not enough pixels sampled per wavelength, discretization effects when estimating derivatives can bias the results. Depending on the inversion and the derivative kernel used, this can cause about a 4% error when there are 9‐10 pixels per wavelength, but the error rapidly increases with fewer pixels per wavelength 79,83,84 . Conversely, when the wavelength becomes much larger than the pixel size, the discrete derivative operations required for some inversion methods are highly affected by low SNR.…”
Section: Good Practices For Mre Publicationsmentioning
confidence: 99%
“…79,83,84 Conversely, when the wavelength becomes much larger than the pixel size, the discrete derivative operations required for some inversion methods are highly affected by low SNR. It has been reported that the accuracy and precision of MRE measurements with direct inversion are optimal when six to nine voxels per wavelength are obtained and the SNR is sufficiently high 84 ; more recent work studies the effects of kernel width and the order of the derivative operators in the inversion. 84 Discussion of results should address this question, and whether the wavelength/pixel ratio is in an appropriate range.…”
Section: Discretization Effectsmentioning
confidence: 99%
“…Wrap-free phase images from unwrapping algorithms and from dual and multiple encoding methods were used for reconstruction of shear wave speed (SWS) maps based on phase-gradient wavenumber recovery to avoid noise amplification by the Laplacian operator which is inevitable in direct inversion techniques [40,41]. SWS is related to tissue stiffness and will be termed as such in the following.…”
Section: Shear Wave Speed Reconstructionmentioning
confidence: 99%
“…As demonstrated in prior work, high shear strain at slip boundaries leads to reconstruction of very low elasticity in the vicinity of the interface 16 . However, most inversion approaches analyze shear strain in a spatially extended neighborhood, causing blurring of localized properties (partial volume effects) due to inversion 28 . Applied to surface regions in cerebral MRE maps, this partial volume–related averaging of very soft (slip interface) properties of CSF with solid cortex properties results in overall softening of surface voxels in conventional MRE of the brain.…”
Section: Discussionmentioning
confidence: 88%